An Exploratory Study of Beef Cattle Farming Systems: A Comparative Analysis of Cut and Carry in Java vs. the Pastoral System in Sumba Island, Indonesia - Setianto, Novie Andri; Sodiq, Akhmad; Sumarmono, Juni; Kii, Wilhelmus Yape; Widiyanti, Rahayu; Haryoko, Imbang (Faculty of Agriculture, 2024)
ABSTRACT. This study aims to explore the differences between beef cattle farming systems in Java and Sumba. The research was conducted using a survey method in three districts, two districts in Central Java and one district in Sumba Island, NTT. Data analysis used a descriptive qualitative approach, with the CATWOE Analysis framework to determine the perspectives of stakeholders involved in the beef cattle farming business system. Beef cattle farming in Java has been characterized by a cut and carry system, while in Sumba with a pasture grazing system. The research shows that the main purpose of cattle rearing in Java is to generate income for the family, so more and more are running enlargement and fattening businesses. Cattle rearing in Sumba is prioritized for savings for traditional purposes. Farmers in Sumba predominantly breed cattle without additional feed to save on maintenance costs. Farmers are still faced with the problem of unfairness in pricing. The study concluded that farmers show adaptive ability in allocating their resources to obtain profits. Differences in farming paradigms need to be considered in the preparation of livestock development programs.(Studi eksploratif pada sistem pemeliharaan sapi potong: analisis komparatif pada sistem cut and carry di jawa dengan sistem penggembalaan pastura di pulau Sumba, Indonesia)ABSTRAK. Peternakan sapi potong di Jawa selama ini dicirikan dengan cut and carry sistem, sedangkan di Sumba dengan sistem penggembalaan di pastura. Penelitian ini bertujuan untuk melakukan eksplorasi lebih mendalam tentang perbedaan sistem usaha peternakan sapi potong di Jawa dengan di Sumba. Penelitian dilakukan dengan metode survey di tiga kabupaten, dua kabupaten di Jawa Tengah dan satu kabupaten di Pulau Sumba, NTT. Analisis data menggunakan pendekatan deskriptif kualitatif, dengan kerangka CATWOE Analysis untuk mengetahui perspektif dari para stakeholders yang terlibat dalam sistem usaha peternakan sapi potong. Penelitian menunjukkan bahwa tujuan utama pemeliharaan sapi di Jawa adalah untuk menghasilkan pendapatan untuk keluarga, sehingga semakin banyak yang lebih menjalankan usaha pembesaran dan penggemukan. Pemeliharaan sapi di Sumba lebih diutamakan untuk tabungan untuk keperluan adat. Peternak di Sumba didominasi pembiakan sapi tanpa tambahan pakan untuk menghemat biaya pemeliharaan. Peternak masih dihadapkan pada permasalahan ketidakadilan dalam penentuan harga. Penelitian menyimpulkan bahwa peternak menunjukkan kemampuan adaptif dalam mengalokasikan sumber daya yang dimiliki untuk memperoleh keuntungan. Perbedaan paradigma beternak perlu untuk diperhatikan dalam penyusunan program pembangunan peternakan.